1987
DOI: 10.7326/0003-4819-106-5-687
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infection by Gentamicin-ResistantStreptococcus faecalis

Abstract: Enterococci with high-level resistance to gentamicin account for 55% of clinical isolates of enterococci found in patients at the Ann Arbor Veterans Administration Medical Center. We prospectively studied cultures obtained from all 100 patients hospitalized from 1 December 1985 through 23 January 1986 on the surgical and thoracic intensive care units and a general medical floor. Ten patients' cultures grew colonies of gentamicin-resistant enterococci--six after admission to the intensive care units and four af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
0
1

Year Published

1987
1987
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(165 citation statements)
references
References 30 publications
5
159
0
1
Order By: Relevance
“…The authors concluded that nosocomial enterococcal bacteremia was usually caused by the patient's own endogenous fecal flora introduced into the bladder with instrumentation of the urinary tract and that there was no evidence of personto-person spread within the hospital (7). This study, which suggests that nosocomial transmission of enterococci may occur, was supported by a second prospective study of gentamicin resistant enterococci by the same authors (10). At the Ann Arbor Veterans Administration Medical Center all patients admitted to an index general medicine ward or surgical intensive care unit (SICU) over a two-month period were followed up with cultures.…”
Section: Modes Of Transmission Of Enterococcimentioning
confidence: 84%
See 3 more Smart Citations
“…The authors concluded that nosocomial enterococcal bacteremia was usually caused by the patient's own endogenous fecal flora introduced into the bladder with instrumentation of the urinary tract and that there was no evidence of personto-person spread within the hospital (7). This study, which suggests that nosocomial transmission of enterococci may occur, was supported by a second prospective study of gentamicin resistant enterococci by the same authors (10). At the Ann Arbor Veterans Administration Medical Center all patients admitted to an index general medicine ward or surgical intensive care unit (SICU) over a two-month period were followed up with cultures.…”
Section: Modes Of Transmission Of Enterococcimentioning
confidence: 84%
“…Using antibiotic sensitivity patterns and plasmid profiles, however, they showed that the urinary tract isolate differed from the rectal or perineal isolate in two out of three cases, suggesting that colonization during catheter insertion, and not rectal or perineal colonization, predisposes to UTI (10). Bacteremia.…”
Section: Epidemiologic Aspects Of Enterococcal Infectionmentioning
confidence: 98%
See 2 more Smart Citations
“…These strains were the first reported strains to be resistant to all aminoglycosides, since the French isolates were susceptible to high-level streptomycin. From 1981 to 1984, the frequency of isolation of E. faecalis strains resistant to high-level gentamicin at the University of Michigan Hospital rose from 0.04 to 3.7% and, by 1987, to 16% of all enterococcal isolates (65,66). Among 159 enterococcal isolates collected from eight U.S. tertiary-care hospitals in six geographic regions between July 1988 and March 1989, 24.5% demonstrated high-level gentamicin resistance (15).…”
Section: Penicillin-aminoglycoside Synergymentioning
confidence: 99%